2014
DOI: 10.1073/pnas.1414135111
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial reactive oxygen species are scavenged by Cockayne syndrome B protein in human fibroblasts without nuclear DNA damage

Abstract: Significance Mitochondria are often considered a source of reactive oxygen species (ROS) that cause damage to cellular components including nuclear DNA. This endogenous damage is thought to underlie neurodegeneration, especially in diseases such as Cockayne syndrome (CS) that lack transcription-coupled DNA repair (TCR). We find no evidence, however, for any nuclear DNA damage from increased mitochondrial ROS. Our results indicate that the neurodegenerative symptoms in CS may be mitochondrial in origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 45 publications
7
38
0
Order By: Relevance
“…5A and Fig. S5A), compatibly with a previous report (9). Moreover, all patientderived cells displayed very high hypoxia-inducible factor-1 (HIF1α) mRNA levels, which are induced by high ROS content (39), compared with controls (Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…5A and Fig. S5A), compatibly with a previous report (9). Moreover, all patientderived cells displayed very high hypoxia-inducible factor-1 (HIF1α) mRNA levels, which are induced by high ROS content (39), compared with controls (Fig.…”
Section: Resultssupporting
confidence: 89%
“…Comparison of these two types of patient' cells indicates that the impaired UV response was uncoupled from oxidative stress and premature aging. In agreement with this finding, higher levels of reactive oxygen species (ROS) were recently reported in mitochondria from CS compared with UV S S and healthy cells (9). CSA and CSB also act as transcription factors, and CSB has been proposed to remodel chromatin (10)(11)(12).…”
supporting
confidence: 58%
“…Because G:C→T:A mutations are a signature of mutagenesis induced by 8-oxo-dG, the most common oxidative lesion in cells (37), this observation alludes to CSB's additional role in oxidative DNAdamage repair (21)(22)(23), loss of which could result in increased oxidative damage-induced mutagenesis. We previously reported that CSB interacts with complex I of the mitochondria to quench surplus reactive oxygen species (38). Given the neurological involvement in CS, further studies on the mutagenic consequences of oxidative DNA damage may be worthwhile for understanding the pathologies seen in CS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, using a host cell reactivation (HCR) assay in which undamaged cells were transfected with plasmids treated prior to transfection to induce the oxidized bases, 8-oxoG or thymine glycol, we have demonstrated that expression of the plasmid-coded lacZ reporter gene is defective in CS cells but not in UV S S cells [36]. A possible explanation for these puzzling results is that the CS defect not only eliminates TCR but that it affects other cellular functions such as transcriptional bypass of oxidative damage [3841], processing of oxidative damage in mitochondria [4245] or defective neurogenesis [46, 47]…”
Section: Dna Repair and Photosensitivitymentioning
confidence: 99%